2016
DOI: 10.1111/coa.12543
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation tube insertion simulation: a literature review and validity assessment of five training models

Abstract: The quality of simulation models is moderate and there is room for improvement. There is a need for new models to be developed or existing ones to be refined in order to construct a more realistic training platform for VTI simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…24,26 The current reality of residency time constraints has sparked the development of multiple feasible task trainers for common procedures. 9,11,19,25,27,28 Use of low-cost, well-described, and readily accessible task trainers in this study makes dissemination and implementation of the described curriculum feasible at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 The current reality of residency time constraints has sparked the development of multiple feasible task trainers for common procedures. 9,11,19,25,27,28 Use of low-cost, well-described, and readily accessible task trainers in this study makes dissemination and implementation of the described curriculum feasible at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The chosen simulator was Jesudason and Smith's (2004) Bradford Grommet Trainer, 12 which was the preferred low-fidelity ventilation tube insertion trainer in a recent review. 13 Two disposable auricular temperature probe covers are arranged in series; the membrane of the internal cylinder is pulled taut by the second probe cover, acting as the tympanic membrane. The simulator was inserted into the right ear of a manikin and draped for enhanced realism.…”
Section: Methodsmentioning
confidence: 99%
“…Mahalingam et al performed a 2015 literature review of 11 simulation models, of which only 5 underwent validity assessment, 2 relied on virtual reality and only 5 were deemed feasible to replicate. 1 The diameter of the tympanic membrane in these models ranged from 6 to 10 mm while the length of the external auditory canal ranged from 2.1 to 4.0 cm. The various materials used for the tympanic membrane included plastic, adhesive tape, latex, vinyl, cellophane and nitrile.…”
Section: Discussionmentioning
confidence: 97%
“…The study concluded that none of these models achieved face or global content validity. 1 In 2008, Uy and Martinez 3 fashioned a do-it-yourself myringotomy model from recycled plastic egg crate, 3-cc plastic syringe, medical tape and modeling clay that then cost approximately PhP 100 (approximately USD 1.90 in 2008 and approximately USD 2.50 or PhP 130 in 2018). However, we believe the materials they used are easily prone to wear and tear and would have to be constantly replaced and refashioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation